2018
DOI: 10.1016/j.carbpol.2018.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional laminarin microparticles for cell adhesion and expansion

Abstract: Microfabrication technologies have been widely explored to produce microgels that can be assembled in functional constructs for tissue engineering and regenerative medicine applications. Here, we propose microfluidics coupled to a source of UV light to produce multifunctional methacrylated laminarin microparticles with narrow distribution of sizes using photopolymerization. The multifunctional microparticles were loaded with platelet lysates and further conjugated with an adhesive peptide. The adhesive peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 34 publications
(46 reference statements)
0
19
0
Order By: Relevance
“…Laminarin is one of the main building blocks of marine biosphere and is currently emerging as an alternative biomaterial for designing different biomedical platforms due to its low viscosity, cytocompatibility, and biodegradability. [ 43,44 ] Diatoms produce around 10 gigatons of laminarin yearly as their storage compound, while kelp forests and beds harbor a wide variety of brown algae such as those of the Laminaria and Eisenia genus that span throughout the Atlantic and Pacific Ocean waters. [ 45 ] In this work, laminarin extracted from Eisenia bicyclis was selected as the natural β ‐glucan polysaccharide for subsequent reprograming of its backbone with aldehyde moieties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Laminarin is one of the main building blocks of marine biosphere and is currently emerging as an alternative biomaterial for designing different biomedical platforms due to its low viscosity, cytocompatibility, and biodegradability. [ 43,44 ] Diatoms produce around 10 gigatons of laminarin yearly as their storage compound, while kelp forests and beds harbor a wide variety of brown algae such as those of the Laminaria and Eisenia genus that span throughout the Atlantic and Pacific Ocean waters. [ 45 ] In this work, laminarin extracted from Eisenia bicyclis was selected as the natural β ‐glucan polysaccharide for subsequent reprograming of its backbone with aldehyde moieties.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, to the best of our knowledge, laminarin has only been processed as a photocrosslinkable biomaterial (i.e., methacrylated). [ 43,44 ] Moreover, the functional properties of adaptable networks with lower molecular weight biopolymers (such as oxLAM) as network‐crosslinking agents remain elusive to date. [ 29,62 ] Aldehyde‐functionalized oxLAM biopolymer can readily bind to amine‐containing biomaterials via Schiff base formation, which is convenient to install dynamic crosslinks with ECM‐mimetic gelatin ( Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, monodisperse droplets of gel precursor solution infused with cells were first generated by a microfluidic device having a flow-focusing geometry, followed by photo-crosslinking to generate cell-laden microgels (Figure 1). Similarly, methacrylate laminarin microparticles were also prepared by combination of microfluidics technology and photopolymerization [67]. Microfluidic-based cell encapsulation by microgels has been applied in studying cellular dynamics and interactions.…”
Section: Fabrication Techniques For Three-dimensional (3d) Cell Micromentioning
confidence: 99%
“…Platelet lysates were loaded in the microparticles and an adhesive peptide was further conjugated on the surface to improve cell adhesiveness and expansion. Moreover, microparticles aggregation linked by the expanded cells was observed to form robust 3D constructs, which suggested that these methacrylate laminarin microparticles could provide a platform for rapid fabrication of large tissue engineered constructs through assembly of cell-laden microparticles by the action of cells [67]. Duan et al [39] constructed chitin microspheres with a nanofibrous architecture using a bottom-up approach.…”
Section: Non-porous Microspheresmentioning
confidence: 99%
“…Because PL-based hydrogels usually suffer from poor mechanical properties and poor stability in vitro , new approaches have emerged in order to overcome these issues [ 8 , 10 ]. Examples are loading or incorporation of PL in scaffolds [ [11] , [12] , [13] ], use of cross-linking agents (e.g. genipin) [ 14 ], or PL modification with cross-linkable groups [ 9 ].…”
Section: Introductionmentioning
confidence: 99%